APLIKASI TEKNOLOGI REVERSE OSMOSIS UNTUK PEMURNIAN AIR SKALA RUMAH TANGGA - Ariyanti, Dessy; Widiasa, I N. (Diponegoro University, 2011)
Initially, commercially available reverse osmosis (RO) systems were intended to use on ships for producing freshwater during long voyages. After the time, many developments have been conducted especially in membraneelement and system configuration. Such developments allow RO systems to be applied for home use with normalplumbing in households. A basic reverse osmosis system consists of a pressurized source of water, a membranesystem, and hoses of pipes that carry off and separate clean water and drain water. There are four types ofhousehold RO system, i.e.: undersink, whole house, multi family, farm and ranch. If a water quality problem isdue to several different contaminants, RO may be the most cost-effective method for their removal.